A COMMERCIAL WEBSITE FOR SINAR TERANG BAG COLLECTIONS AND HOME INDUSTRY: A WAY TO MAKE THE EXISTING CUSTOMERS KNOW ITS PRODUCTS AND INCREASE ITS SALES - Rachel Kurniawan; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2015)
The purpose of making this Business Communication Final Project was to solve Sinar Terang’s problems. The problem was related to its products’ existence. Only few existing customers of Sinar Terang knew that Sinar Terang has its own bags. For that reason, it was difficult for Sinar Terang to sell its bags more. Therefore, the problem was how to make Sinar Terang’s existing customers know its bags without coming to the store and how to make Sinar Terang’s bags more popular. The solution to these problems was making a bilingual commercial website which consists of “Updates” part, “About Us” part, “Our Collections” part, “Made to Order” part, “Our Customers” part, and “Contact Us” part. This website would indeed solve Sinar Terang’s problem because for the existing customers, they could see Sinar Terang’s bags including the information without coming to the store. Also, Sinar Terang could attract new customers through this website.